Economic Approach to Forest Management for Wood Production - Rustagi, Krishna P. (Indian Forester, 1972)
In spite of being renewable, forest resource is not unlimited 18 extent and India is no exception. Like all other sectors of economic activity, forests should be managed efficiently for maximum satisfaction of public needs and at the same time should provide adequate revenue surplus to the states. Though the forests serve a variety of functions, production of wood (timber and fuel wood) continues to be the principal activity. With a limited budget investments in reforestation and other management activities for wood production must satisfy the tests Of maximum productivity and profitability, This paper outlines an approach which should help in rationalizing the forest management planning for wood production.